2019
DOI: 10.3390/molecules24132417
|View full text |Cite
|
Sign up to set email alerts
|

LIR Motif-Containing Hyperdisulfide β-Ginkgotide is Cytoprotective, Adaptogenic, and Scaffold-Ready

Abstract: Grafting a bioactive peptide onto a disulfide-rich scaffold is a promising approach to improve its structure and metabolic stability. The ginkgo plant-derived β-ginkgotide β-gB1 is a highly unusual molecule: Small, hyperdisulfide, and found only in selected ancient plants. It also contains a conserved 16-amino-acid core with three interlocking disulfides, as well as a six-amino-acid inter-cysteine loop 2 suitable for grafting peptide epitopes. However, very little is known about this recently-discovered family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…The hyperstability of β-lybatide can be attributed to its compact cystine-knot structure, which is known to confer the high metabolic stability in CRPs, particularly against endopeptidases (Loo et al, 2016;Nguyen et al, 2014;Tam et al, 2018;Wong et al, 2016). These results are in agreement with our previous studies as well as those by others, in which CRPs of 2 to 5 kDa with three to five disulfides are known to be hyperstable and able to resist heat, acid and enzymatic degradation due to their compact and multiple disulfide-constrained structures (Dutta, Huang, To, & Tam, 2019;Tam, Wang, Wong, & Tan, 2015;Wong et al, 2017a;Wong, Tan, Xiao, & Tam, 2017b).…”
Section: Stability Of β-Lybatidesupporting
confidence: 92%
“…The hyperstability of β-lybatide can be attributed to its compact cystine-knot structure, which is known to confer the high metabolic stability in CRPs, particularly against endopeptidases (Loo et al, 2016;Nguyen et al, 2014;Tam et al, 2018;Wong et al, 2016). These results are in agreement with our previous studies as well as those by others, in which CRPs of 2 to 5 kDa with three to five disulfides are known to be hyperstable and able to resist heat, acid and enzymatic degradation due to their compact and multiple disulfide-constrained structures (Dutta, Huang, To, & Tam, 2019;Tam, Wang, Wong, & Tan, 2015;Wong et al, 2017a;Wong, Tan, Xiao, & Tam, 2017b).…”
Section: Stability Of β-Lybatidesupporting
confidence: 92%
“…Similarly, this result agrees with β-ginkgotide isolated from G. biloba, which contained an LIR-like motif (DEYGCI) and induced cytoprotective effects in both cardiomyocytes and neuronal cells [398]. Additionally, eT1 promotes cell migration, which is a hallmark of wound healing.…”
Section: Bioactivity Of Eleutidesupporting
confidence: 85%
“…To examine the effects of eleutide eT1 in hypoxia stress, the rat cardio-myoblast H9c2 cells were employed and the procedure was followed according to Dutta et al [398]. The cells were cultured with or without eT1 and incubated in a normoxic and hypoxic environment for 48 h before evaluating the cell viability via MTT assay.…”
Section: Cell Viability Assay Of Eleutidementioning
confidence: 99%
“…This example provides a precedent to develop plant-derived highly disulfided peptides for oral administration. Furthermore, we have recently reported that such cystine-dense peptides with MW 2–4 kDa appeared much more common than previously thought [ 12 , 14 , 15 , 18 , 19 ]. Noteworthy examples include roseltides [ 15 , 18 , 19 ], β-ginkgotides [ 14 ], and ginsentides [ 12 , 17 ], which exhibit diverse bioactivities with potential therapeutic applications.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, we have recently reported that such cystine-dense peptides with MW 2–4 kDa appeared much more common than previously thought [ 12 , 14 , 15 , 18 , 19 ]. Noteworthy examples include roseltides [ 15 , 18 , 19 ], β-ginkgotides [ 14 ], and ginsentides [ 12 , 17 ], which exhibit diverse bioactivities with potential therapeutic applications. These cell-penetrating peptides offer certain advantages in targeting intracellular proteins and the potential for oral administration.…”
Section: Discussionmentioning
confidence: 96%